1991
DOI: 10.1164/ajrccm/144.4.756
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Patterns of Upper Respiratory Illness andPneumocystis cariniiPneumonia in Homosexual Men

Abstract: The relationship between self-reported upper respiratory illness symptoms (URI) and human immunodeficiency virus Type 1 (HIV-1) was examined in homosexual men using semiannual visits from 1984 to 1988. Temporal and geographic patterns of Pneumocystis carinii pneumonia (PCP) diagnosis in these men during the same time period are also described. URI, including acute sinusitis, was reported more often by 916 HIV-1-seropositive participants than by 2,161 seronegative participants (32.21 versus 28.86% p less than 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 2 publications
3
17
1
Order By: Relevance
“…In a large retrospective study about AIDS‐defining diseases in European countries, Delmas et al [3] indicated that the risk of pneumocystosis in UK was more than twice as high as that in Portugal. Similar observations were made according to the climate of cities in the USA [6]. Only one study reported a correlation between low rainfall and new cases of pneumocystosis [8].…”
Section: Resultssupporting
confidence: 71%
“…In a large retrospective study about AIDS‐defining diseases in European countries, Delmas et al [3] indicated that the risk of pneumocystosis in UK was more than twice as high as that in Portugal. Similar observations were made according to the climate of cities in the USA [6]. Only one study reported a correlation between low rainfall and new cases of pneumocystosis [8].…”
Section: Resultssupporting
confidence: 71%
“…They noted a higher incidence of PCP in AIDS patients from northern regions, as did another recent study from Europe [2]; similar findings were reported by the American Multicenter AIDS Cohort Study (MACS) with regard to AIDS patients before the availability of prophylaxis from 1986 to 1988 [3]. In our analysis, cohorts of AIDS patients with the highest rates of PCP also had the highest incidence of upper respiratory tract infections [3].…”
supporting
confidence: 90%
“…and K.R.D., unpublished data). Even though seasonal differences in antibody levels were not found, climatic factors, such as temperature and humidity, have been shown to influence the occurrence of PCP [2932] and might have had an effect here.…”
Section: Discussionmentioning
confidence: 78%